La place du monde anglophone dans les livrets d’Eugène Scribe - Matthieu Cailliez (Caliban: French Journal of English Studies)
Eugène Scribe (1791-1861) was the author of 425 plays, including 94 librettos for comic operas and thirty librettos for operas, performed in nineteen Parisian theatres, one provincial theatre and three foreign theatres. During his lifetime, these works ensured their author widespread national and international success. The aim of this contribution is a general study of the place of the English-speaking world in Scribe’s opera and opera-comique librettos, whether they be adaptations of English-language authors, works with English characters or plots set in an English-speaking country (England, Scotland, Wales, Ireland, USA and British India). English history in general, and the reigns of Edward III, Henry VII, Elizabeth I and Charles II in particular, serve as a thematic reservoir of librettos for at least four of Scribe’s opéras-comiques. Three novels by Walter Scott and a play by Shakespeare inspired two comic opera librettos and one Italian opera libretto.